Bifunctional catalytic effect of Mo2C/oxide interface on multi-layer graphene growth - Seda Kizir (Nature Portfolio, 2021)
Abstract The role of the Mo2C/oxide interface on multi-layer graphene (MLG) nucleation during a chemical vapor deposition (CVD) process is investigated. During the CVD process, MLG growth is only observed in the presence of a Mo2C/SiO2 interface, indicating that the chemical reactions occurring at this interface trigger the nucleation of MLG. The chemical reaction pathway is explained in four steps as (1) creation of H radicals, (2) reduction of the oxide surface, (3) formation of C–C bonds at O–H sites, and (4) expansion of graphitic domains on the Mo2C catalyst. Different Mo2C/oxide interfaces are investigated, with varying affinity for reduction in a hydrogen environment. The results demonstrate a catalyst/oxide bifunctionality on MLG nucleation, comprising of CH4 dehydrogenation by Mo2C and initial C–C bond formation at the oxide interface.